2003
DOI: 10.1017/s0266467403003031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ingestion by bats and birds on seed germination of Stenocereus griseus and Subpilocereus repandus (Cactaceae)

Abstract: Effects of seed passage through digestive tracts of principal animal dispersers (bats and birds) on seed germination were investigated for two columnar cactus species, Stenocereus griseus and Subpilocereus repandus. In general, seeds ingested showed more rapid germination times and higher overall germination rates than untreated seeds. The bat Glossophaga longirostris, and the birds Mimus gilvus and Tachyphonus rufus seem to be the most efficient cacti dispersers in terms of quality of treatment. The increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…Although the passage of seeds through the digestive tracts of bats did not improve germination percentage, seed ingestion by bats modified, to a large or small extent, the speed at which M. macroura seeds germinated, a result consistent with that reported by Naranjo et al (2003), who tested germination of Stenocereus griseus and Subpilocereus repandus seeds when passing through the digestive tract of the Miller's long-tongued bat Glossophaga longirostris. Sosa (1997) also found that the ingestion of Stenocereus thurberi by bats does not improve germination and contributes only to dispersal by transportation of seeds.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Although the passage of seeds through the digestive tracts of bats did not improve germination percentage, seed ingestion by bats modified, to a large or small extent, the speed at which M. macroura seeds germinated, a result consistent with that reported by Naranjo et al (2003), who tested germination of Stenocereus griseus and Subpilocereus repandus seeds when passing through the digestive tract of the Miller's long-tongued bat Glossophaga longirostris. Sosa (1997) also found that the ingestion of Stenocereus thurberi by bats does not improve germination and contributes only to dispersal by transportation of seeds.…”
supporting
confidence: 85%
“…Sosa (1997) also found that the ingestion of Stenocereus thurberi by bats does not improve germination and contributes only to dispersal by transportation of seeds. As pulp can act as a germination inhibitor and can also increase the probability of seed deterioration with fungi (Naranjo et al 2003), it is possible that removal of the inhibiting factor present in the pulp resulted in higher germination of control seeds in our experiment. Most studies indicated that seed germination of many plant species improved after ingestion by bats (Fleming & Heithaus 1981, Lieberman & Lieberman 1986, Figueiredo & Perin 1995, Shilton et al 1999.…”
mentioning
confidence: 86%
“…The fact that the peak abundance of fruits coincides with our highest number of records of chiropteran visitation gives additional support to the idea of synchrony between these two events. Furthermore, the three species of bats recorded in our study are known to disperse cacti seeds (Naranjo et al, 2003). Novoa, Cadenillas, and Pacheco (2011) recorded Pallas's longtongued bats feeding on P. leucocephalus in a separate study.…”
Section: Frugivore Diversitymentioning
confidence: 52%
“…Our knowledge of frugivory patterns in all these taxa is scarce and lists of visitors to three species of the genus Pilosocereus (P. leucocephalus, P. polygonus, and P. purpusii), and a few closely related genera, are the only information available for the entire clade. Three groups of vertebrates, birds, bats, and reptiles are listed in previous studies (Kissling, Böhning-Gaese, & Jetz, 2009;Naranjo, Rengifo, & Soriano, 2003;Ruiz, Santos, Cavelier, & Soriano, 2000;Silva, 1988;Silvius, 1995;Tschapka, Sperr, Caballero-Martínez, & Medellín, 2008;Wendelken & Martin, 1988). Beyond those lists of visitors, Soriano et al (1999) made the only available study that attempts to quantify the relative F I G U R E 1 The Rancho San Ignacio, a private estate near the city of Xalapa, Veracruz, Mexico, has a population of the woolly torch (Pilosocereus leucocephalus) that grows over an ancient basalt lava flow covered with tropical deciduous forest importance of various frugivore visitors to two columnar cacti in Venezuela.…”
Section: Natural History Of Pilosocereus Leucocephalusmentioning
confidence: 99%
See 1 more Smart Citation